Ricardo's Notes on Malthus - Mason, E. S. (Quarterly Journal of Economics, 1928)
Journal Article Ricardo's Notes on Malthus Get access E. S. Mason E. S. Mason Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 42, Issue 4, August 1928, Pages 684–696, https://doi.org/10.2307/1882540 Published: 01 August 1928